Enhancing Engineering Students’ Flexible Communication Skills through Digital Learning Environments to Support International Cooperation - Saienko, Nataliia; Bogdan, Zhanna (Journal of Interdisciplinary Studies in Education, 2026)
Communication skills are a key component of the flexible skills required for future engineering professionals, supporting effective interaction with colleagues, clients, and international partners. This study investigates the effectiveness of a specially designed digital English-language course in cross-cultural communication for developing engineering students’ flexible communication skills at Kharkiv National Automobile and Highway University. A pedagogical experiment conducted during the 2024–2025 academic year involved an experimental group (n = 65) and a control group (n = 63). The experimental group was taught using innovative digital methods, whereas the control group followed conventional instruction. The findings revealed statistically significant improvements in the experimental group, confirming the effectiveness of the proposed instructional approach.